Proceedings of 37th International Cosmic Ray Conference — PoS(ICRC2021) 2021
DOI: 10.22323/1.395.0832
|View full text |Cite
|
Sign up to set email alerts
|

Very High Energy Gamma-ray Emission from the Binary System LS I +61 303

Abstract: LS I +61°303 is one of around ten gamma-ray binaries detected so far which has a spectral energy distribution dominated by MeV-GeV photons. It is located at a distance of 2 kpc and consists of a compact object (black hole or neutron star) in an eccentric orbit around a 10-15Be star, with an orbital period of 26.496 days. The binary orbit modulates the emission ranging from radio to TeV energies. A second, longer, modulation period of 1667 days (the super-orbital period) has also been detected from radio to TeV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
321
3
32

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(373 citation statements)
references
References 16 publications
17
321
3
32
Order By: Relevance
“…It is possibly due to the activation of ER resident protein caspase-12, which activates the cytoplasmic caspase-3 via TNFα during the ER stress [30]. Increased caspase-3 activation alters the mitochondrial membrane depolarization leading to mitochondrial dysfunction [31]. Recent studies also suggested that microglial cell function is a prerequisite for appropriate brain function and important for the maintenance of neuronal circuitry, and dysfunction of microglia leads to abnormal behavior or neural dysfunction [32].…”
Section: Discussionmentioning
confidence: 99%
“…It is possibly due to the activation of ER resident protein caspase-12, which activates the cytoplasmic caspase-3 via TNFα during the ER stress [30]. Increased caspase-3 activation alters the mitochondrial membrane depolarization leading to mitochondrial dysfunction [31]. Recent studies also suggested that microglial cell function is a prerequisite for appropriate brain function and important for the maintenance of neuronal circuitry, and dysfunction of microglia leads to abnormal behavior or neural dysfunction [32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have examined how physiological reactivity to the Cyberball task differs based on psychological symptoms. Lidia et al (2021) found that individuals with borderline personality disorder exhibited a further decline in RSA after the inclusion condition of the Cyberball task. Lambe, Craig, and Hollenstein (2019) found that peer victimization was more strongly associated with depressive symptoms when youth also demonstrated blunted RSA reactivity to the Cyberball task.…”
Section: Journal Of Emotion and Psychopathologymentioning
confidence: 95%
“…Synthesis of different diamines from limonene via oxidation and subsequent amination. [ 78,79 ] Yields are given as overall yields depending on the synthesis route.…”
Section: Terpene‐based Amines and Lactams And Their Use In Polymer Sy...mentioning
confidence: 99%
“…In a patent published in 2019, Kobilka et al introduced the synthesis of four different diamines from limonene (Figure 7a–d). [ 78 ] Depending on the reaction conditions, limonene was oxidized to four different oxygenized species. In two cases (Figure 7a,b), limonene was oxidized to the α , β ‐unsaturated ketones 10 and 13 , the position of the ketone group depending on the type of reactant.…”
Section: Terpene‐based Amines and Lactams And Their Use In Polymer Sy...mentioning
confidence: 99%